Geochemistry of the granitoid plutons of the Brookville terrane, Saint John, New Brunswick, and implications for development of the Avalon Zone - Eby, G.; Currie, K. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1996)
The Brookville terrane forms a fault-bounded region, underlain mainly by plutonic and high-grade metamor-phic rocks, flanked on one side by a typical Avalonian terrane (Caledonia terrane), and separated from a typical Avalonian terrane (Mascarene terrane) on the other side by the Silurian Kingston Dike Complex. Mafic plutons of the Brookville terrane were derived from a source similar to that of the continental margin basalts of the Coldbrook Group of the Caledonia terrane. Some sialic plutons were probably derived from mixtures of this basaltic component with a component similar to bulk crust. Major element data for most of the plutons fall on smooth curves on Harker diagrams, suggesting that crystal fractionation is the major process controlling the evolution of individual plutons. Trace element modelling indicates that this fractionation was largely due to the removal of hornblende, plagioclase, and alkali feldspar. The presence of A2~type granites of similar age (ca. 550 Ma) in the Caledonia terrane (Bonnell Brook), Brookville terrane (Fairville), and Mascarene terrane (Lingley) suggest that these terranes were amalgamated by 550 Ma. Subsequent magmatism in the Brookville terrane was characterized by emplacement of plutons typical of continental margin magmatism. This period of magmatism ended with the emplacement of A2-type plutons, suggesting that magmatism in the Brookville terrane ceased during post-subduction extension.